Overview of Body Shaming Experiences in Early Adolescents at Junior High School Jember - Tri Pramesuari, Ni Komang; Fitria, Yeni; Deviantony, Fitrio; Rasni, Hanny; Kurniyawan, Enggal Hadi (Jurnal Ilmiah Kesehatan, 2024)
Early adolescents undergo numerous changes for the first time, leading them to adapt to these transformations. Among the most conspicuous changes is the physical transformation that renders adolescents susceptible to body shaming, which can have detrimental effects on their mental health. This study aims to delineate the experience of body shaming among early adolescents at one junior high school in Jember. The research employed an analytic observational design with a cross-sectional approach involving 297 respondents. Proportional stratified random sampling was utilized as the sampling technique, and a body shaming experience questionnaire was administered. The findings revealed that 167 respondents (56.2%) experienced body shaming to a moderate extent. The significance of this research lies in its potential to serve as a reference for providing health education regarding the prevalence of body shaming and its impact on mental health. Such education aims to enhance adolescent mental health within the school environment.